2013
DOI: 10.1371/journal.pntd.0002054
|View full text |Cite
|
Sign up to set email alerts
|

New Approaches with Different Types of Circulating Cathodic Antigen for the Diagnosis of Patients with Low Schistosoma mansoni Load

Abstract: BackgroundSchistosomiasis mansoni is a debilitating and sometimes fatal disease. Accurate diagnosis plays a key role in patient management and infection control. However, currently available parasitological methods are laborious and lack sensitivity. The selection of target antigen candidates has turned out to be a promising tool for the development of more sensitive diagnostic methods. In our previous investigations, the use of crude antigens led to false-positive results. Recently, focus has been given to hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 43 publications
1
28
0
Order By: Relevance
“…Furthermore, in a study performed in an endemic area in the State of Minas Gerais, 100% of the individuals evaluated 30 days after schistosomiasis treatment resulted negative for serum CCA (10) . This indicates that levels of serum and urine CCA and CAA decrease significantly some weeks after treatment, constituting a biomarker for schistosomiasis cure.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, in a study performed in an endemic area in the State of Minas Gerais, 100% of the individuals evaluated 30 days after schistosomiasis treatment resulted negative for serum CCA (10) . This indicates that levels of serum and urine CCA and CAA decrease significantly some weeks after treatment, constituting a biomarker for schistosomiasis cure.…”
Section: Introductionmentioning
confidence: 99%
“…Our ROC curve analyses showed highly accurate power of discrimination indicating almost perfect test. Using a similar set of samples, Sarhan et al (2014) showed AUC of 0.99 and 0.87 using SEA and SWAP antigens [78], and Grenfell et al (2013) showed 0.94 using recombinant CCA [79]. Even crude extracts of worm antigens can be used for ELISA, such assays would require infrastructure to maintain the parasite cycle and the complexity of large-scale production and standardization.…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies utilizing other S.mansoni recombinant proteins also showed better results than K-K performed by 2 slides in low-endemic areas. The recombinant CCA showed 100% sensitivity and 96% specificity by IgG detection in chronic individuals using magnetic microspheres [79]. The IgG-ELISA using recombinant 200-kDa tegumental protein demonstrated 90% sensitivity and 93.3% specificity with a strong correlation with egg burden in the same set of individuals [75].…”
Section: Discussionmentioning
confidence: 99%
“…Native CCA glycoprotein contains 0-linked poly ( Lewis X ) carbohydrate chains with approximately 25 repeating units. Carbohydrate chains containing multiple Lewis X determinants have been identified on several glycolipids not only from schistosomes but also from other parasites, from human adenocarcinomas and also, circulating granulocytes carry relatively high abundance of branched N-linked polysaccharides having Lewis X repeating units, as previously discussed [17]. Another alternative is the detection of Schistosoma sp.…”
Section: Introductionmentioning
confidence: 93%